Isolation and characterization of poly(A)-containing polyoma "early" and "late" messenger RNAs. - Rosenthal, L J (1976)
During late lytic infection of mouse kidney cell cultures polyoma 16S and 19S (late 19S RNA) were isolated by oligo(dT)-cellulose chromatography. Approximately 60-80% of total cytoplasmic polyoma RNA contained tracts of poly(A) which were retained by oligo(dT)-cellulose. Early in lytic infection when viral DNA synthesis and the production of capsid protein are blocked by the addition of 5-fluorodeoxyuridine, approximately 100% of polyoma "early" 19S RNA was quantitatively retained by oligo(dT)-cellulose indicating the presence of poly(A) tracts on most 19S mRNA molecules. In addition, 2 classes polyoma RNA, synthesized after the onset of cellular RNA synthesis under conditions where DNA synthesis is inhibited with 5-fluorodeoxyuridine, were found to contain tracts of poly(A). These species sedimenting at 16S and 19S in aqueous sucrose density gradients were also quantitatively retained by oligo (dT)-cellulose.